VALUE OF THE COMPANY AND IT’S FACTORS (STUDY IN INDONESIA’S MINING COMPANY SECTOR) - Sigit Handoyo; Kinanthi Putri Ardiami; Rifqi Setya Perdana (Universitas Tidar, 2022)
Many financial and non-financial factors that can affect the value of the company. This study aims to examine the effect of tax avoidance, disclosure of corporate social responsibility, firm size and sales growth on firm value in mining sector companies listed on the Indonesia Stock Exchange for the period 2014-2018. This research uses descriptive statistical test, classical assumption test and multiple linear regression test. The results showed that the disclosure of Corporate Social Responsibility and sales growth had a positive effect on firm value, while tax avoidance and firm size had no effect on firm value.